Sv. Jurij ob Taboru, Sv. Miklavž in Črni Vrh v Spodnji Savinjski dolini sredi 19. stoletja - Baš, Angelos (Etnolog. Nova vrsta (Ljubljana), 2008)
The article publishes the principal data from Georg Göth's Topographie des Herzogtums Steiermark from the 1st half of the 19th century (the topography's material on the districts of Maribor and Celje has been preserved in copies at the Institute of Slovene Ethnology, SRC, SASA since 1880); the data relate to the small agrarian settlements of Sv. Jurij ob Taboru (seat of the parish), Sv. Miklavž, and Črni Vrh in the Lower Savinja Valley. The inhabitants of these settlements made their living from agriculture and stockbreeding. They produced enough grain and fodder for the needs of the people and animals. When the crops fell short they bought grain and fodder either in the neighbouring municipalities or at the fairs in Braslovče. A glassworks operated in Sv. Miklaž from 1814, producing chalk glass that was similar to milk glass and was mainly for general use (bottles, jugs, glasses, etc.). The glassworks, which has to date been overlooked in the history of glassworks in Slovenia, had six melting pots. The factory operated for about forty years until approximately the mid 19th century. An additional income in Sv. Miklavž and its close environs was provided by boating on the Sava. The Sava was an important traffic route in the Austrian Empire in the first half of the 19th century, but it lost its significance after the construction of the Southern Railway in the mid 19th century.
Keywords: Slovenci; Slovenes; Spodnja Savinjska dolina; ethnology; etnologija; history; zgodovina; Göthova topografija